Learning and Assessment of HOTS among Senior High School Economics Students - Kennedy Acheampong; Dadang Dahlan; Disman; Edi Suryadi; Muhamad Arief Ramdhany (Jurnal Pendidikan dan Pengajaran, 2023)
In today's world, where globalization is rapidly increasing, critical thinking, rationality, and tolerance are essential for personal and interpersonal well-being. The study aims to analyze the impact of teaching methods, self-concept, and assessment on students' higher-order thinking skills (HOTS) in economics in senior high school (SHS). The research subjects involved 220 economics students from three SHS. The study used a quantitative survey method with the use of a designed questionnaire and used ordinal logistic regression to find the correlations between variables. The findings suggest that teaching methods, self-concepts, and assessment have a significant impact on students' understanding of economics subjects by promoting higher-order thinking skills. To improve Ghana's educational system and meet the Sustainable Development Goals (SDGs) 2030, the study also underlines the necessity of HOTS-oriented assessment in classroom instruction. Therefore, the study recommends the use of various instructional strategies, such as open-ended questions and practical problem-solving tasks that encourage students to manipulate unfamiliar or novel situations, rather than relying on recall or restatement of previously taught material. The implication of this study is that curriculum developers should take into consideration a well-structured question in the curriculum that will elicit students' high-order thinking skills.